Imaging Appropriateness in Pediatric Radiology during COVID-19 Pandemic: A Retrospective Comparison with No COVID-19 Period - Giampiero Bottari; Giandomenico Stellacci; Davide Ferorelli; Alessandro Dell’Erba; Maurizio Aricò; Marcello Benevento; Giuseppe Palladino; Biagio Solarino (Children, 2021)
During the COVID-19 pandemic, the number of accesses to the Pediatric Emergency Department (pED) in Italy sharply decreased by 30%. The purpose of this study is to evaluate how this novel setting impacted on management of children with trauma, and the use and appropriateness of imaging studies in such patients at the pED. All imaging studies performed in patients with trauma at the pED of a tertiary children’s Hospital during the first wave of the COVID-19 pandemic (between March and May 2020) were reviewed, in comparison with a control time interval (March to May 2019). In the pre-COVID control era, 669 imaging studies documented bone fractures in 145/568 children (25.5%). In the COVID-era, 79/177 (44.6%) pediatric patients showed bone fractures on 193 imaging studies. Comparative analysis shows a 71% decrease in imaging studies, and the proportion of negative imaging studies (with no evidence of bone fractures) dropped in 2020 by 19% compared to the 2019 control era (p < 0.001). The sharp decrease of negative studies suggests that the rate of appropriateness was higher during COVID-era, suggesting some attitude toward defensive medicine in the previous control year, as a result of some degree of imaging inappropriateness. The impact of a pandemic on emergency medicine may offer a unique opportunity to revisit diagnostic and therapeutic protocols in pediatrics.